A Numerical Modeling of Formation of Volcanic Geothermal Reservoir - Alamta Singarimbun (Indonesian Journal of Physics, 2010)
The aim of the research is to develope the thermal energy from volcanic geothermal reservoir. One of the prospec of the geothermal energy for the future is the utilization of volcanic geothermal reservoir. The using of numerica simulation is important to clarify the thermal processes in a fluid reservoir beneath an active volcano. The fluid reservoir is a permeable zone, where the magmatic water discharged from magma mixes with the downgoing meteoric water. The flow rate of magmatic water becomes the mass and energy input to the reservoir. Finally, the fluid go to the earth’s surface as vapor and liquid. The main physical parameters of the fluid reservoir cover pressure, temperature, enthalpy and enthalpy. The Finite Difference Method based on mass and heat balance equations is used to obtain these parameters. The parameters reperesent the thermal state of the fluid in the reservoir. The fluid phase in the reservoir changes with time. These processes interpret the development of the energy in a geothermal reservoir.